THE URGENCY OF APPLYING DOMESTIC VIOLENCE SCREENING MECHANISM FOR DIVORCE MEDIATION IN RELIGIOUS COURT - Tirtawening T; Rini Maryam (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractThe mediation process in divorce cases is vulnerable to power relation imbalances and domestic violence. Domestic Violence Screening is a set of questions delivered by the mediator to the parties in Religious Court to examine whether domestic violence happens in the marriage. Domestic Violence Screening in mediation is not well known in Indonesia however it has been vastly used in many countries such as USA and Australia. This research tried to explained the benefit of Domestic Violence Screening in divorce mediation in Religious Court and identify whether it can be applied in Indonesia. Screening allows for: a) identification of power relation imbalance and domestic violence; b) domestic violence recording; and c) provide referral services for domestic violence victims. IntisariMediasi perkara perceraian rentan mengalami ketimpangan relasi kuasa dan kekerasan dalam rumah tangga/KDRT. Skrining KDRT (screening domestic violence) merupakan sejumlah daftar pertanyaan yang diajukan oleh mediator kepada para pihak yang berperkara di pengadilan agama untuk memeriksa apakah telah terjadi kekerasan selama ikatan pernikahan. Meskipun skrining KDRT belum dikenal di Indonesia namun telah digunakan secara luas dalam mediasi di berbagai negara. Penelitian ini bertujuan untuk memberikan gambaran sejauh mana manfaat skrining KDRT pada saat mediasi perkara perceraian dan apakah skrining tersebut dapat diterapkan di Indonesia. Keberadaan skrining memudahkan untuk: (a) mengidentifikasi terjadinya ketimpangan relasi kuasa dan kekerasan domestik sebagai faktor penyebab perceraian, (b) melakukan pendataan kasus KDRT, dan (c) memberikan layanan rujukan kepada korban KDRT.